The hole in the wall: how the film ‘27 steps of may’ portrays stages of grief and acceptance - Muhammad Iqbal Qeis; Rista Ihwanny (Cogent Arts & Humanities)
27 Steps of May is an Indonesian film directed by Ravi Bharwani that centers around the life of May and her father. Throughout this 112-minute film, the two of them continue to repeat the same routine for eight years following May’s traumatic experience as a sexual assault survivor. This film is important to be analyzed because it highlights a marginalized issue of sexual assault. This study aims to uncover the visual narrative of the film to see how the film 27 Steps of May portrays grief and acceptance in living as a sexual assault survivor. Using visual methodologies with Peircean semiotics approach, this study will analyze whether the film further popularized the Kübler-Ross model of grieving stages or tried to present another perspective through its dominant visual images. The result shows that the film portrays different stages of grief by focusing on the process of grieving for May using the medium in the form of the hole in the wall. This finding shows that the film took a different approach by breaking through the popular model known as the five stages of grief. This study implies that there is a need to redefine the stages of grief so that personal emotions and actions experienced in grieving can be accommodated.